The problem of highly effective cleaning of air from dust - Batluk, V. A.; Romantsov, E. V.; Klymets, V. M. (Національний університет "Львівська політехніка", 2013)
This article deals with the problem of providing high performance apparatuses for cleaning air from dust in various branches of industry in order to reduce hazardous emissions to the level of conforming to the sanitary-hygienic norms. The article describes new trends in the development of dust catching apparatuses based on the use of centrifugal-inertial forces, permitting to improve significantly the dust catching efficacy.
Keywords: dust catching; air cleaning; pollution; centrifugal; cyclone